1990
DOI: 10.1007/bf02244116
|View full text |Cite
|
Sign up to set email alerts
|

Effects of scopolamine, trimipramine and diazepam on explicit memory and repetition priming in healthy volunteers

Abstract: The effects of scopolamine, an anticholinergic drug, of trimipramine, a tricyclic antidepressant with both anticholinergic and sedative properties, of diazepam and a placebo, on explicit memory and repetition priming were assessed using a free-recall task and a word-stem completion task. Forty-eight healthy volunteers took part in this double-blind study. Diazepam provoked a dissociation between free recall, which was profoundly impaired, and word completion, which was spared. No significant changes in memory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
18
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 11 publications
4
18
1
Order By: Relevance
“…In contrast to most previous studies, however (Danion et al, 1990;Knopman, 1991;Schifano and Curran, 1994), our results with scopolamine also demonstrate a cholinergic modulation of repetition priming. We suggest that these differences could be attributable to a lower active dose used in these previous studies (subcutaneous or intramuscular injections are centrally less effective) so that priming was not significantly impaired.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to most previous studies, however (Danion et al, 1990;Knopman, 1991;Schifano and Curran, 1994), our results with scopolamine also demonstrate a cholinergic modulation of repetition priming. We suggest that these differences could be attributable to a lower active dose used in these previous studies (subcutaneous or intramuscular injections are centrally less effective) so that priming was not significantly impaired.…”
Section: Discussioncontrasting
confidence: 99%
“…Although cholinergic modulation of learning, and corresponding neuronal activity, has been shown in many explicit learning paradigms (Caine et al, 1981;Frith et al, 1984;Nissen et al, 1987;Rusted and Warburton, 1988;Curran et al, 1991a;Furey et al, 2000), its effects on behavioral measures in implicit paradigms is more controversial. Psychopharmacological and electrophysiological evidence suggests an absence of cholinergic modulation on repetition priming, because several studies found no behavioral (Danion et al, 1990;Knopman, 1991;Schifano and Curran, 1994) or neuronal ) modulation of repetition effects after administration of the cholinergic antagonist scopolamine. By contrast, manipulations of GABAergic neurotransmitter systems with the benzodiazepine lorazepam impairs behavioral indices of repetition priming in humans (Knopman, 1991;Buffett-Jerrott et al, 1998;Vidailhet et al, 1999).…”
mentioning
confidence: 99%
“…The behavioral impairments with lorazepam were consistent with prior studies using picture-fragment completion, word-fragment completion, or wordstem completion tasks Vidailhet et al 1994;Vidailhet et al 1999;Danion et al 1992;Brown et al 1989). Behavioral impairments of repetition priming with scopolamine, on the other hand, were not in line with the majority of prior studies (Knopman 1991;Danion et al 1990;Schifano and Curran 1994), and we suggested that these differences could be caused by a lower active dose used in these previous studies (see Thiel et al 2001 for discussion).The rationale for the present study was to further investigate GABAergic and cholinergic modulation of repetition priming, using a paradigm involving face recognition (Ellis et al 1990). This paradigm investigates priming of faces and its modulation by familiarity (i.e., famous vs. unfamous faces).…”
supporting
confidence: 73%
“…Note that scopolamine did not affect task accuracy per se, as the number of correctly identified faces in this group did not differ from placebo or lorazepam. This argues against the idea that a perceptual mechanism underlies priming impairments after scopolamine and is consistent with a prior study showing that scopolamine does not affect face recognition (Rammsayer et al 2000).Prior psychopharmacological studies were not able to induce impairments in priming paradigms when giving scopolamine before study phase (Knopman 1991;Danion et al 1990;Schifano and Curran, 1994) (see Thiel et al 2001) for discussion). Because we have previously found that scopolamine attenuates priming in a word-stem completion paradigm (Thiel et al 2001), the present finding, that scopolamine also impairs priming in a face recognition paradigm, confirms again that cholinergic systems are important for the behavioral expression of repetition priming.…”
supporting
confidence: 73%
See 1 more Smart Citation